INTEGRAÇÃO LOCAL COMO SOLUÇÃO DURÁVEL: ANÁLISE SOBRE A CONVERGÊNCIA ENTRE O DIREITO INTERNACIONAL DOS REFUGIADOS E O DIREITO INTERNACIONAL DOS DIREITOS HUMANOS - Andressa Santana Arce (2022)
This research is about one of the durable solutions proposed for the refugee problem by the United Nations High Comissioner for Refugees: local integration. The question that is posed is how should the concept of local integration be comprehended considering the convergence between International Refugee Law and Human Rights International Law. Thus, the main objective of this reasearch consists in demonstrating which are the legal frameworks that local integration should have in order to become compatible with a broad protection of refugees’ human rights, in the light of Antônio Augusto Cançado Trindade`s perspective about the convergence of the axes of international protection of human rights, as well as Vincent Chetail’s understanding about the need of recognition of the existence of a cross-fertilization between International Refugee Law and Human Rights Law. The research is justified not only because of the great number of refugees allocated in Third World Countries and neighbor Countries but also considering that few researches regarding the durable solutions proposed by UNHCR were found in Brazilian literature, specially, concerning local integration. The theoretical and methodological focus of the research is sociocritical of law, considering that the referenced authors in the study analyze critically the globalization phenomenon, the refugee definition contained in the Geneva Convention of 1951 and the New York Protocol of 1967, as well as the limitations of the protection guaranteed by these documents, and they propose a more universal approach – less conditional – towards the protection of refugees’ rights. Still concerning the methodology of the research, in terms of form, is qualitative, in terms of ends, descriptive and exploratory and, in terms of means, bibliographic and documental. The deductive method is the one utilized. It was verified that the right of asylum should be recognized as a human right and that States’ discretion regarding the implementation of local integration should be eliminated, as all traditional solutions have a volition component, which means that, if a refugee does not choose neither voluntary repatriation nor resseatlement, opting, therefore, for local integration in the host country, there will be no choice but to adopt suitable measures to implement it, or else access to basic rights will be denied and human rights will be, thus, violated.